Resolving Kirkuk lessons learned from settlements of earlier ethno-territorial conflicts ; prepared for U.S. Forces-Iraq - Hanauer, Larry; Miller, Laurel E. (RAND National Defense Research Inst., 2012)
Abbreviations -- Introduction -- Kirkuk -- Approaches to resolving ethno-territorial disputes -- Territorial compromise -- Power-sharing arrangements -- Other influences on solutions to ethno-territorial disputes -- Society -- Role of elites -- Role of third parties -- Case studies -- Brcko -- Background -- Relevance to Kirkuk -- Mostar -- Background -- Relevance to Kirkuk -- Northern Ireland -- Background -- Relevance to Kirkuk -- Jerusalem -- Background -- Relevance to Kirkuk -- Lessons for Kirkuk and how they can be applied -- Substantive issues -- Sovereignty and territorial control -- Power-sharing -- Autonomy -- Political elites and ethnic outbidding -- Security -- Dispute resolution process -- The roles of third parties -- International administration -- Timelines -- Deferral of contentious issues as "final status" issues -- "Grand bargains" -- Bottom-up versus top-down solutions -- Confidence-building measures -- Society and local leadership -- Can outside actors facilitate a solution for Kirkuk?